Preventive and therapeutic effect of vitamin D on depression-like behavior in a mouse adolescent depression model and its association with BDNF protein expression - Yang, Xueping; Miao, Junxiao; Huang, Yinglin; Li, Lili; Zhuang, Gengsen (Frontiers in Psychiatry, 2024)
Introduction Previous studies in different populations have shown that vitamin D supplementation may reduce depression levels. In adolescents, vitamin D deficiency has been identified as a factor contributing to the onset of depression. This study aimed to establish a model of adolescent depression in mice by using the scientific unpredictable chronic mild stress (UCMS) model and to preliminarily evaluate the effect of vitamin D on the occurrence and development of depression and whether it is related to the protein expression of the BDNF pathway. Methods The UCMS method was used to establish a model of adolescent depression in 4-week-old C57BL/6 male mice, randomly divided into five groups: Control group, Stress group, Stress+ low-dose group, Stress+ medium-dose group, Stress+ high-dose group. At the same time as chronic stress, the administration groups were given intramuscular injections of different doses of vitamin D. After 8 weeks, behavioral tests, including the forced swimming test (FST) and open field test (OFT), were performed on each group of mice, along with recording of indicators, blood vitamin D level detection, and brain tissue western blot analysis. Results The results showed a significant difference in vitamin D levels among mice in different groups after 8 weeks (P=0.012). The results of behavioral testing showed a significant difference in the static time of forced swimming among the groups (P<0.001). Compared with the UCMS group, the static time of mice with vitamin D injection was significantly reduced (P<0.001). The total number of times mice entered the central area, the total distance of movement, and the time spent in the central area significantly increased after vitamin D injection compared with the UCMS-only group (all P<0.001). There was no significant difference in the expression of BDNF in the brain tissues of experimental mice (P>0.05). Discussion In conclusion, in the mouse adolescent depression model, appropriate vitamin D supplementation can reduce the occurrence of stress-induced depression. Furthermore, vitamin D deficiency may also serve as a potential risk factor for depression.